2019
DOI: 10.3892/mmr.2019.10011
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA‑0044073 is upregulated in atherosclerosis and increases the proliferation and invasion of cells by targeting miR‑107

Abstract: Circular RNAs (circRNAs) are endogenous non-coding RNAs implicated in atherosclerosis. The aim of the present study was to explore the function of circRNA-0044073 in atherosclerosis. Reverse transcription quantitative polymerase chain reaction assays were used to measure the expression levels of circRNA-0044073, microRNA (miRNA/miR)-107, janus kinase 1 (JAK1), signal transducer and activator of transcription 3 (STAT3), B-cell lymphoma 2 (Bcl-2) and v-myc avian myelocytomatosis viral oncogene homolog (c-myc) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 52 publications
1
69
0
Order By: Relevance
“…Recently, a report demonstrated that avian leucosis virus targets circ-Vav3 and then sponges gga-miR-375 to promote epithelial-mesenchymal transition [38], indicating that a microorganism could directly influence the formation, expression and function of circRNAs, and the mysterious of circRNA is suggested in increasing numbers of studies [30,38,39]. In order to verify these, the expression level of circRNAs was examined by qRT-PCR in AD-like mice (PCR primers are listed in Table 1).…”
Section: Circnf1-419 Changes the Intestinal Physiology And Gut Microbmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a report demonstrated that avian leucosis virus targets circ-Vav3 and then sponges gga-miR-375 to promote epithelial-mesenchymal transition [38], indicating that a microorganism could directly influence the formation, expression and function of circRNAs, and the mysterious of circRNA is suggested in increasing numbers of studies [30,38,39]. In order to verify these, the expression level of circRNAs was examined by qRT-PCR in AD-like mice (PCR primers are listed in Table 1).…”
Section: Circnf1-419 Changes the Intestinal Physiology And Gut Microbmentioning
confidence: 99%
“…Studies have shown that in the brain, where the level of circRNA is significantly higher, some circRNAs consist mainly of portions of the multi-exon 5′ untranslated region (5′UTR), suggesting that functions of these multi-exon 5′UTR of genes and/or circRNA is new [28]. Increasing numbers of circRNAs function in the brain, including circPDE4B [29], circRNA-0044073 [30], and circHIPK3 [31], as well as in heart failure [32,33], human cancer (Josh N, et al) [34] and other diseases [35], suggesting that circRNAs are crucial functional molecules in mammals. Thus, studying the roles of circRNAs on the gut-brain axis is important.…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that circRNAs are involved in numerous pathological mechanisms underlying cVds, such as AS, immune response, apoptosis, cell proliferation, autophagy, cell senescence and myocardial repair (103)(104)(105)(106)(107)(108)(109). Emerging evidence has suggested that circRNAs play an important role in the occurrence and development of cVd (110).…”
Section: Regulatory Mechanisms Of Circrnas On Cvdmentioning
confidence: 99%
“…The proliferation of cells involved in the cardiovascular system plays an important role in the development of cVds, such as hypertension, AS and restenosis (110). circRNAs serve an important role in the development of cVds (103,111). Shen et al (103) demonstrated that circRNA-0044073 is highly expressed in patients with AS.…”
Section: Regulatory Mechanisms Of Circrnas On Cvdmentioning
confidence: 99%
“…Beyond that, by repressing miR-9, circSMAD2 impedes the activation of STAT3 and MEK/ERK pathways in migration and epithelial-mesenchymal transition [122]. CircRNA-0044073 promotes the proliferation of cells by sponging miR-107 and activating the JAK/STAT signaling pathway [123]. There are still many factors that regulate adipogenesis which may be the targets of circRNAs, such as miR-143 [124], miR-130 [125], miR-145 [126], miR-181a [127], and let-7 [128].…”
Section: Potential Circrna Regulatory Pathmentioning
confidence: 99%